Registered report: Melanoma genome sequencing reveals frequent PREX2 mutations - Chroscinski, Denise (eLife, 2014)
The Reproducibility Project: Cancer Biology seeks to address growing concerns about reproducibility in scientific research by conducting replications of 50 papers in the field of cancer biology published between 2010 and 2012. This Registered Report describes the proposed replication plan of key experiments from ‘Melanoma genome sequencing reveals frequent PREX2 mutations’ by Berger and colleagues, published in Nature in 2012 (Berger et al., 2012). The key experiments that will be replicated are those reported in Figure 3B and Supplementary Figure S6. In these experiments, Berger and colleagues show that somatic PREX2 mutations identified through whole-genome sequencing of human melanoma can contribute to enhanced lethality of tumor xenografts in nude mice (Figure 3B, S6B, and S6C; Berger et al., 2012). The Reproducibility Project: Cancer Biology is a collaboration between the Center for Open Science and Science Exchange, and the results of the replications will be published by eLife. DOI: http://dx.doi.org/10.7554/eLife.04180.001